Continuous Surgical Decompression for Solitary Bone Cyst of the Jaw in a Teenage Patient - Lluís Brunet-Llobet; Eduard Lahor-Soler; Elias Isaack Mashala; Jaume Miranda-Rius (Case Reports in Dentistry)
Background. A solitary bone cyst or simple bone cyst is a nonneoplastic osseous lesion, with no epithelial lining, also considered as a pseudocyst. These lesions, with an intact bony wall and fluid-filled, are frequently discovered by chance in radiological studies. The etiopathogenesis has not been studied in depth, and the management remains controversial. Case Presentation. We present a clinical case of a 15-year-old boy who underwent an orthopantomography to assess the development and position of the third molars during a routine postorthodontic check-up. By chance, the X-ray identified an asymptomatic radiolucent image in the left jaw, measuring 12.0 mm×17.8 mm and compatible with a solitary bone cyst involving teeth 35 and 36. We describe our technique for performing minimally invasive decompression of the lesion using a microperforated catheter. We describe the entire course of the follow-up, both clinical and radiological, until complete cure. Conclusions. This straightforward continuous decompression technique poses no problems for the patient, has a low risk of sequelae, and is clearly cost-effective. In view of the highly satisfactory evolution, whenever possible, we favor this minimally invasive technique for the treatment of solitary bone cysts in the jaw.